The Blind Side of Art: Visual Impairment as a Resource in the Work of Mexican Artists - Monika Dubiel (Przeglad Socjologii Jakosciowej, 2022)
Disability studies is a dynamically developing discipline; however, it usually focuses on the Anglophone world. Scholars representing this field often concentrate on deconstructing popular stereotypes and revealing hidden systemic discrimination. Although more and more initiatives are taken up – such as disability pride – it seems that an affirmative approach to disability remains in the minority. This article is a proposal for going beyond the mentioned schemes. Entering the area of the Latin American culture, I try to verify whether the findings of disability studies can be confirmed there. Proposing the interpretation of dis-ability in terms of resource, I want to broaden the affirmative perspective on disability.